Banking Default Not Disburse Deposits Of Deceased Customers Analysis Of Decision No. 201/PDT.G/2018/PN MDN - Febrianto Lubis, Yudhi; Sembiring, Rosnidar; Lisa Andriati, Syarifah (Jurnal Hukum Replik, 2025)
This research examines the issue of banks refusing to disburse joint deposits by analyzing Medan District Court Decision Number 201/Pdt.G/2018/PN Mdn through a normative juridical approach. The main findings indicate that the absence of explicit regulations in legislation regarding banking authority in disbursing joint deposits causes banks to implement varied internal policies. In the case studied, the bank refused disbursement due to incomplete requirements and unclear legal relationship between the plaintiff and the deceased customer, although heirs should legally receive protection as consumers of banking services. This research highlights the importance of clearer regulations to protect customer interests in banking transactions